O professor-gestor, as tecnologias digitais e just in time teaching: um olhar sob a experiência de professores-gestores educacionais - Alencastro, Fernanda de Oliveira (Universidade do Vale do Rio dos Sinos, 2023)
The theme of this study was the academic managers, digital technologies, and the active methodology called Just in Time Teaching. The main objective was to investigate the role of academic manager, and how they perceive the use of digital technologies and the active just-in-time teaching methodology, based on the experience of academic managers related to na Edtech. This is a research with a qualitative approach, for which the procedure adopted was that of multiple case studies, with collection carried out from a previous organizer and open interviews with a semi-structured script speech. As main results, is possible to mention the identification of common steps in the paths and trajectories of the academic managers interviewed, their challenges, and motivations. It was also possible to identify recommendations for technologies and ways of using them in the classroom and management, as well as the perceptions of these professionals regarding the Just in Time Teaching active methodology strategy. Furthermore, a reference document was created sharing practices recommended by the interviewees for other teachers who are adhering to the dual role of academic manager.
Keywords: Professor-gestor; Ensino sob medida; Tecnologias digitais; Academic manager; Just in time teaching; Digital technologies; ACCNPQ::Ciências Humanas::Educação